Diseño de un modelo gestión turístico para 5 iniciativas de turismo comunitario del cantón Archidona - Quishpe Quishpe, Ángel Andrés (2019)
The present project has as main objective the development of a design of a model of tourism management for 5 initiatives of community tourism of the canton Archidona with the purpose of generating a welfare socio-economic in the initiatives of community tourism through the improvement of the tourism management, the fomentation of the associativity between communities and the implementation of channels of promotion and marketing. The first chapter includes topics related to community tourism and its evolution, tourist destinations, tourism systems and management models, to facilitate the reader a greater understanding of the project. As for the methodology, the project used a qualitative research approach through the application of the following methods: technical data sheets, free interviews, problem tree, strategy tree, objective tree and observations not structured, these methodologies allowed to collect relevant information for the development of the following chapters. After the application of the research methodologies, the analysis of the situational characterization of the territory was carried out, the characterization of the tourist system and based on the results, continued with the design phase of the proposal, where, was created the logical frame matrix. Finally, in the last chapter of development of the proposal, we defined the tourist product that covers the 5 community tourism initiatives through associativity in the following elements: tour packages, itineraries, interpretive script, cost analysis, marketing strategies, promotion, monitoring and evaluation, managed by the responsible stakeholders according to their competitiveness, which are reflected in the established tourism management model.